Analisis Kewenangan Badan Pertimbangan Aparatur Sipil Negara dalam Pemeriksaan Banding Administratif terhadap Keputusan Pemberhentian Aparatur Sipil Negara sebagai Upaya Perlindungan Hukum - Fachrie Putra Riyadi; Agus Dimyati (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the authority of the State Civil Apparatus Advisory Body (BPASN) in examining administrative appeals against decisions to dismiss State Civil Apparatus (ASN) and the legal protection provided through this mechanism. The study uses a normative juridical method with a statutory regulatory approach and a conceptual approach. The results show that BPASN's authority is based on Law Number 30 of 2014 and is further regulated in Government Regulation Number 79 of 2021. The administrative appeal mechanism provides repressive legal protection before dispute resolution through the State Administrative Court. However, there remains disharmony in the regulations after the enactment of Law Number 20 of 2023 and limitations in the objects of administrative appeals that affect the certainty and effectiveness of legal protection for ASN.